Cold-Activated Lipid Dynamics in Adipose Tissue Highlights a Role for Cardiolipin in Thermogenic Metabolism - Lynes, Matthew D. (Cell Rep, 2018)
Thermogenic fat expends energy during cold for temperature homeostasis, and its activity regulates nutrient metabolism and insulin sensitivity. We measured cold-activated lipid landscapes in circulation and in adipose tissue by MS/MS(ALL) shotgun lipidomics. We created an interactive online viewer to visualize the changes of specific lipid species in response to cold. In adipose tissue, among the approximately 1,600 lipid species profiled, we identified the biosynthetic pathway of the mitochondrial phospholipid cardiolipin as coordinately activated in brown and beige fat by cold in wild-type and transgenic mice with enhanced browning of white fat. Together, these data provide a comprehensive lipid bio-signature of thermogenic fat activation in circulation and tissue and suggest pathways regulated by cold exposure.